Factors influencing family planning practice among husbands in the district of Marang, Terengganu , 1996 - Hasnilawati Mohamad; Hanafiah Mohd Salleh (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross sectional study was carried out among husbands in the district of Marang, Terengganu to identify the practice of family planning and the factors influencing it in Mac,1996. 234 respondents were chosen by simple random sampling based on their working place. Data was collected using self administered questionaires. Majority of respondents (98.7%) were Malays and had education up to secondary levels (67.9%). Mean income for respondents is 941.45 :t 710.56. The results showed that 98.3% of respondents had knowledge about family planning with the pill being the most well-known method (92.3%).Percentage of current-users are 33.3% (n=78).Among those with high knowledge only 32.8% (n=119) are current-users.Study has identified reasons such as for spacing (98.7%), methods are better than traditional (91.0%), presence of husbands' support (87.2%), confidence with the methods (87.2%) and highly available (83.3%) were statistically significance with the practice of family planning. While factors like having high values on children (92.9%), fear of side-effects (79.5%), wanting children (77.6%), husbands' opposition (71.8%) and against religion (69.2%) were noted to act as barriers to the acceptance of family planning. These factors were , found to be statistically significance between acceptors and non-acceptors ( p value < 0.05). Practice is also noted to be influenced significantly by attitudes and perceptions (p < 0.05). Study also showed that attitudes, knowledge and previous experience significantly influenced their perceptions towards family planning (p value < 0.05). There was no significant relationship as regards to husbands' and wives' age, age at marriage,education level and sosioeconomic status ( p value > 0.05). In conclusion, involvement of husbands in determining the practice of family planning is significantly influenced by 5 factors against, 5 stimulant factors, perception and previous experience. However religion and high value of children were noted to be statistically significance with practise as well as perceptions which make them the most important f factor in family planning.